DESAIN MEDIA “E-STORYBOOK SAYU WIWIT” BERBASIS KEARIFAN LOKAL CERITA RAKYAT BANYUWANGI KELAS VII SMPN 2 BANGOREJO (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to design learning media based on local wisdom used to increase reading interest of seventh grade students at SMPN 2 Bangorejo, Banyuwangi. As well as knowing the quality of learning media based on the assessment of three experts, namely material experts, media experts and learning experts. The development of this media uses the ADDIE method, namely analysis, design, development, implementation and evaluation (product assessment). This research is at the level of development level one in the research process, namely researchers conduct research to produce product design designs that are tested internally. The design of the learning media "E-Storybook Sayu Wiwit" begins with an analysis of student needs, which is continued with the design of learning media development planning, and product development through the heyzine platform. The results of the validation of the three experts, namely media experts, material experts and learning experts, show that the media "E-Storybook Sayu Wiwit" is in the very feasible category in all aspects, so that the media is suitable for use in Javanese language learning. These things make the "E-Storybook Sayu Wiwit" media not only a means of supporting learning activities, but also a means of preserving Banyuwangi's local wisdom through learning activities in schools in an effort to increase students' interest in literacy.